1976
DOI: 10.1007/bf01385945
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of copper(II) and nickel(II) triazacycloalkane complexes

Abstract: SummaryCopper(ll) and nickel(ll) complexes of triazacycloalkanes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1978
1978
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This strategy was not successful, however, despite numerous attempts either to add nitrite salts to Tp RR‘ Cu I compounds or to reduce preformed Tp RR‘ Cu II −NO 2 - complexes. 17b,18b Reasoning that nitrite coordination to a Tp RR‘ Cu I fragment might be disfavored in the nonpolar solvents most amenable for the handling of hindered Tp RR‘ complexes because of charge considerations (Tp RR‘ is a monoanion, making the copper(I) fragment neutral and a derived nitrite adduct anionic), we turned to the sterically hindered, neutral macrocycles 1,4,7-triisopropyl-1,4,7-triazacyclononane (L i -Pr 3 ) and 1,4,7-tribenzyl-1,4,7-triazacyclononane (L Bn 3 ) recently reported by Wieghardt and co-workers. The trialkyl substituents borne by these molecules render them and their complexes soluble in many organic solvents and prevent deleterious bis(ligand) complex (L 2 Cu) formation, as seen with the unsubstituted 1,4,7-triazacyclononane few examples of copper(I) complexes of these ligands existed at the outset of our work …”
Section: Resultsmentioning
confidence: 93%
“…This strategy was not successful, however, despite numerous attempts either to add nitrite salts to Tp RR‘ Cu I compounds or to reduce preformed Tp RR‘ Cu II −NO 2 - complexes. 17b,18b Reasoning that nitrite coordination to a Tp RR‘ Cu I fragment might be disfavored in the nonpolar solvents most amenable for the handling of hindered Tp RR‘ complexes because of charge considerations (Tp RR‘ is a monoanion, making the copper(I) fragment neutral and a derived nitrite adduct anionic), we turned to the sterically hindered, neutral macrocycles 1,4,7-triisopropyl-1,4,7-triazacyclononane (L i -Pr 3 ) and 1,4,7-tribenzyl-1,4,7-triazacyclononane (L Bn 3 ) recently reported by Wieghardt and co-workers. The trialkyl substituents borne by these molecules render them and their complexes soluble in many organic solvents and prevent deleterious bis(ligand) complex (L 2 Cu) formation, as seen with the unsubstituted 1,4,7-triazacyclononane few examples of copper(I) complexes of these ligands existed at the outset of our work …”
Section: Resultsmentioning
confidence: 93%
“…Two types of copper(II) complexes of cyclic triamines have been reported: (1) bis complexes which likely contain the CuN6 chromophore with tetragonally distorted octahedral stereochemistry6•7 and (2) dimeric species containing chloro and/or hydroxy bridges.7 The larger ring ligands apparently have a propensity toward the formation of the chloroand hydroxy-bridged dimers. 7 We have isolated a copper(II) complex of the [ll]aneN3, [Cu([11]aneN3)2] ( 03)2• 20, and we have studied its infrared and electronic spectra and magnetic susceptibility. The infrared spectrum indicates that nitrate is present as the free ion35 with bands observed at 825 (m, sp), 1370 (vs, br), and 707 cm"1 (w, sp).…”
Section: Discussionmentioning
confidence: 99%
“…The series of cyclic triamines presents a nearly ideal system to study the properties of metal complexes which contain ligands with similar coordinative tendencies yet which progressively distort the stereochemical environment of the metal. Several investigations of metal complexes of cyclic triamines have appeared in the literature, and the interest in these and similar cyclic compounds where one or more nitrogen atoms are replaced by other heteroatoms continued to grow. The extra stability of [9]aneN 3 complexes has been well documented, and the work with the remaining congeners suggested that these cyclic amines behave similarly.…”
Section: Introductionmentioning
confidence: 99%